Low Bone Mineral Density in Chinese Adults with Nonalcoholic Fatty Liver Disease - Ran Cui; Hui Sheng; Xue-Fei Rui; Xiao-Yun Cheng; Chun-Jun Sheng; Ji-Ying Wang; Shen Qu (International Journal of Endocrinology)
Aim. To investigate bone metabolic characteristics in Chinese adults with nonalcoholic fatty liver disease (NAFLD). Methods. A total of 224 patients (99 males and 125 postmenopausal females) were recruited and divided into 4 groups: males without NAFLD, males with NAFLD, females without NAFLD, and females with NAFLD. Bone mineral density (BMD) was evaluated according to body mass index (BMI), waist circumference (WC), and serum biomarkers. β cell function was evaluated by HOMA2%B, HOMA2%S, and HOMA2IR. Results. Males in the NAFLD group had lower BMD of the right hip and the femoral neck (0.852±0.117 versus 0.930±0.123, P=0.002; 0.736±0.119 versus 0.812±0.132, P=0.004), and females had lower BMD of the right hip (0.725±0.141 versus 0.805±0.145, P=0.002) even after adjusted for weight, BMI, waist, HDL, and ALT. There was no significant difference in bone metabolic markers between patients with and without NAFLD. NAFLD was an important factor that affected the bone; moreover, the effect attenuated when HOMA2IR entered into the model (R2=0.160, β=−0.172, and P=0.008). Conclusions. NAFLD exerts a detrimental effect on BMD in both males and females. Insulin resistance may play an important role in this pathophysiological process.